Analysis of the dynamics of maximum oxygen consumption during continuous and interval swimming - E.Yu. , Kolganova; O.E. , Ponimasov; A.O. , Mironov; I.S. , Maryin (Theory and Practice of Physical Culture, 2026)
Objective of the study is to compare the nature of physiological responses to continuous and interval training regimes in swimming to exhaustion. Methods and structure of the study. Eleven qualified male swimmers were tested in continuous and interval swimming at maximum aerobic speed to exhaustion. Respiratory parameters, VO2max, heart rate, blood lactate concentration and ratings of perceived exertion were measured. The nature of physiological responses to continuous and interval training regimes in swimming to exhaustion was assessed by comparing these indicators. Results and conclusions. Continuous and interval training regimes at maximum aerobic speed are both able to elicit the maximum VO2max response prior to exhaustion. Interval swimming consisting of 100-metre series with 15-second rest periods is an effective means of increasing the time during which maximum VO2 values are sustained and contributes to an increase in maximum oxygen uptake.